CLINICALLY DELIVERABLE OPTUNE AND DEEP BRAIN STIMULATOR GENERATED ELECTRICAL FIELDS HAVE VARIABLE EFFICACY ON DIFFERENT TYPES OF BRAIN TUMOUR. (3rd October 2018) - Branter, Joshua; de los Angeles Estevez-Cebrero, Maria; Grundy, Richard; Basu, Surajit; Smith, Stuart
Abstract: INTRODUCTION: Phase III trials of Tumour Treating Fields (TTFields) (Optune) have shown potentially positive results in both primary and recurrent adult Glioblastoma multiforme (GBM) patients. These results have given credence to electromagnetic fields, presenting a new treatment paradigm for brain tumour patients. Here we present investigations into repurposing deep brain stimulation (DBS) electrodes as a novel delivery method of therapeutic electric fields to high grade brain tumours and compare to TTFields treated cell lines. METHODS: Medtronic DBS electrodes were inserted into cell culture flasks and delivered electric fields over a range of frequencies and intensities to a panel of GBM, Medulloblastoma and Ependymoma cell lines. Inovitro is the laboratory based TTFields delivery system. Inovitro was used to deliver TTFields over a range of clinically relevant frequencies (100-400kHz) to a panel of paediatric GBM, Medulloblastoma and Ependymoma cell lines. Differences in the effects of both treatments on cell viability, cell cycling, long-term effects of treatment, as well as genome-wide expression were analysed. RESULTS Both DBS electric fields and TTFields negatively affect cell proliferation and viability of brain tumour cell lines. The magnitude of these effects were dependent upon frequency and intensity. Cells treated with either modality were re-seeded and growth rates were compared to non-treated cells. The treated cells experienced significantly slower growth rates following treatment. Cell cycle analysis revealed that DBS treated cells have significant levels of G0 phase accumulation relative to control flasks, while TTFields treated cells demonstrated greater levels of G2 M phase accumulation across all panels of cell lines tested. The effects of electrotreatment on gene expression will be discussed. CONCLUSIONS: Both treatment modalities have demonstrated efficacy against our array of brain tumour cell lines. The treatments likely have differing mechanisms of action at the cellular level and this is reflected in the differences that have been observed.